2015
DOI: 10.1007/s13277-015-4547-z
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of WWP2 inhibits adhesion, invasion, and migration in liver cancer cells

Abstract: The role and clinical implication of the WWP2 E3 ubiquitin ligase in liver cancer are poorly understood. In the current study, we investigated the expression level of WWP2 and its functions in cell adhesion, invasion, and migration in liver cancer. We used real-time PCR to detect the expression of WWP2 in liver cancer and adjacent samples from the People's Hospital of Lishui and also analyzed The Cancer Genome Atlas (TCGA) RNA-seq data by bioinformatics. Migration and invasion were detected by transwell analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Accumulating evidence has indicated that WWP2 plays a crucial role in the pathogenesis in various types of tumors; however, the underlying mechanisms are not fully understood [43]. On the one hand, the oncogenic role of WWP2 has been well documented in many types of tumors, including oral cancer, endometrial cancer, liver cancer, lung cancer, and glioma [44][45][46][47][48]. On the other hand, WWP2 has been shown to act as a tumor-suppressive gene in ovarian cancer and multiple myeloma [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that WWP2 plays a crucial role in the pathogenesis in various types of tumors; however, the underlying mechanisms are not fully understood [43]. On the one hand, the oncogenic role of WWP2 has been well documented in many types of tumors, including oral cancer, endometrial cancer, liver cancer, lung cancer, and glioma [44][45][46][47][48]. On the other hand, WWP2 has been shown to act as a tumor-suppressive gene in ovarian cancer and multiple myeloma [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most stimulated inflammation-related genes, CXCL10 codes for a chemokine involved in the recruitment of immune cells and associated with HCC recurrence and poor survival [36]. CXCL10 and its receptor CXCR3 were reported to promote migration and invasion in HCC cell lines [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The large‐scale genome analyses have revealed the molecular characteristics associated with HCC OS . However, most studies focused on miRNA, mRNA, gene, and protein expression . With knowledge growing, the functional role of lncRNAs in tumorigenesis and development also represents a significant untapped resource for HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] However, most studies focused on miRNA, mRNA, gene, and protein expression. [26][27][28][29][30] T A B L E 3 (Continued) growing, the functional role of lncRNAs in tumorigenesis and development also represents a significant untapped resource for HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%